OCCURRENCE OF SEPIA TRYGONINA (ROCHEBRUNE) (CEPHALOPODA: SEPIIDAE) IN GULF OF MANNAR - Sarvesan, R (Indian Journal of Fisheries, 2011)
The report confirms the occurrence of the cuttlefish, Sepia trygonina(Rochebrune), in Indian waters. A brief description of the species based onspecimens of one male and one female collected from Gulf of Mannar offTuticorin is given.